Working remotely? Selection, treatment, and the market for remote work - Natalia Emanuel; Emma Harrington (Federal Reserve Bank of New York, 2023)
How does remote work affect productivity and how productive are workers who choose remote jobs? We estimate both effects in a U.S. Fortune 500 firm's call centers that employed both remote and on-site workers in the same jobs. Prior to COVID-19, remote workers answered 12 percent fewer calls per hour than on-site workers. When the call centers closed due to COVID-19, the productivity of formerly on-site workers declined by 4 percent relative to already-remote workers, indicating that a third of the initial gap was due to a negative treatment effect of remote work. Yet an 8 percent productivity gap persisted, indicating that the majority of the productivity gap was due to negative worker selection into remote work. Difference-in-differences designs also indicate that remote work degraded call quality- particularly for inexperienced workers-and reduced workers' promotion rates. In a model of the market provision of remote work, we find that firms were in a prisoner's dilemma: all firms would have gained from offering comparable remote and on-site jobs, but any individual firm was loathe to attract less productive workers.
Keywords: J24; L23; L84; M54; 330; remote work; work-from-home; worker productivity; selection